Giải: 

Ta có \(\lim u_n\) =\(\lim \frac{1}{n}= 0\); \(\lim v_n= \lim (-\frac{1}{n}) = 0\).

Do ${u_n} = \frac{1}{n} > 0$ và ${v_n} = – \frac{1}{n} < 0$ với \(∀ n\in {\mathbb N}^*\)

, nên \(f(u_n)= \sqrt{\frac{1}{n}}+1\) và \(f(v_n) = -\frac{2}{n}\).

Từ đó \( \lim f(u_n)= \lim (\sqrt{\frac{1}{n}}+ 1) = 1\); \(\lim f(v_n)= lim (-\frac{2}{n}) = 0\).

Vì \(u_n→ 0\) và \(v_n → 0\), nhưng \(\lim f(u_n) ≠  \lim f(v_n)\) nên hàm số \(y = f(x)\) không có giới hạn khi \(x → 0\)


0 Bình luận

Trả lời

Avatar placeholder